Phase Separation: A New Dimension to Understanding Tumor Biology and Therapy - Xingwen Wang; Minqiao Lu; Yi Zhang; Jiangwen Ma; Ying Hu (MedComm – Oncology)
ABSTRACT Liquid–liquid phase separation (LLPS) plays a critical role in orchestrating various cellular processes, such as gene expression, signal transduction, and protein synthesis, by compartmentalizing cellular components without membrane boundaries. Emerging research has illuminated how dysregulated LLPS is integral to cancer development by influencing tumorigenesis, metastasis, immune system evasion, and resistance to therapy. The subtle differences in LLPS are crucial for understanding cancer progression and finding new treatments. However, despite its significant implications in oncology, the potential of specifically targeting LLPS in cancer therapy has not been thoroughly investigated. This review delves into the mechanisms of LLPS, exploring physiological triggers and their consequences in cancer biology. We discuss the profound impact of LLPS on the hallmarks of cancer and outline innovative strategies aimed at targeting LLPS. These strategies include the direct inhibition of phase condensate formation and the modulation of related signaling pathways. Although targeting LLPS poses several challenges, such as specificity and delivery methods, it represents a promising frontier in cancer treatment, potentially revolutionizing how we approach cancer therapy. This review emphasizes the academic and therapeutic importance of LLPS, advocating for it as an exciting and valuable target for future cancer treatment strategies.